2014
DOI: 10.1073/pnas.1318786111
|View full text |Cite
|
Sign up to set email alerts
|

Elevated morning cortisol is a stratified population-level biomarker for major depression in boys only with high depressive symptoms

Abstract: Major depressive disorder (MD) is a debilitating public mental health problem with severe societal and personal costs attached. Around one in six people will suffer from this complex disorder at some point in their lives, which has shown considerable etiological and clinical heterogeneity. Overall there remain no validated biomarkers in the youth population at large that can aid the detection of at-risk groups for depression in general and for boys and young men in particular. Using repeated measurements of tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
78
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(85 citation statements)
references
References 51 publications
7
78
0
Order By: Relevance
“…This result was entirely unexpected, as it contradicts some of the previous scientific literature on this issue. Nevertheless, this unexpected result could represent a promising finding in this field of research since recent epidemiological studies have suggested some limitations of morning salivary cortisol levels in predicting high risk of developing initial MDE onset in young adult females (Owens et al, 2014). According to our results, it is probable that sAA could overcome this limitation in future studies.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…This result was entirely unexpected, as it contradicts some of the previous scientific literature on this issue. Nevertheless, this unexpected result could represent a promising finding in this field of research since recent epidemiological studies have suggested some limitations of morning salivary cortisol levels in predicting high risk of developing initial MDE onset in young adult females (Owens et al, 2014). According to our results, it is probable that sAA could overcome this limitation in future studies.…”
Section: Discussionmentioning
confidence: 49%
“…Although the studies reviewed in the previous paragraphs highlight the usefulness of cortisol in particular (especially when it is measured in form of the CAR) as an early predictor of a future triggering of a first MDE in adolescents (without gender differences in the majority of the reviewed studies), a recent and robust epidemiological study that examined a wide cohort showed that the predictive capacity of morning cortisol levels could be influenced by gender, thereby increasing misunderstanding of these initial results (Owens et al, 2014). Specifically, these researchers observed that in the total sample of 1858 participants, morning cortisol was associated with a high risk of depression exclusively in male participants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…McEwen, 2012McEwen, , 2013. These results are also of interest in relation to evidence relating levels of post awakening cortisol secretion as a risk factor for future psychopathology (Halligan et al, 2007;Mannie et al, 2007;Owens et al, 2014).…”
Section: Discussionmentioning
confidence: 78%
“…13,14 Additionally, MFQ scores above the 75th percentile are an established behavioural marker for clinical diagnosis of major depression. 22 The Youdin Index was calculated to determine the clinical cutoff point, because it maximises sensitivity and specifi city, 23 thereby increasing correct classifi cation of individuals with and without depression.…”
Section: Discussionmentioning
confidence: 99%